2013
DOI: 10.1007/s11920-013-0429-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Childhood Physical Abuse and Neglect: A Review

Abstract: According to 2010 CDC estimates, 1 in 5 US children have experienced maltreatment. Risk factors for child maltreatment include child characteristics such as non-compliance and diagnostic conditions that increase caregiver burden. Parent characteristic risk factors include parental mental illness and low social support. New developments in radiologic evaluation of child maltreatment will be reviewed. New findings in evidence based psychotherapies for childhood maltreatment will be discussed. A review of the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…(25) A meta-analysis of education programmes was conducted to determine non-cognitive developmental benefits of parenting and early childhood education programmes, as this information was not available in existing systematic reviews. The maltreatment review updated the Lancet 2009 series article on prevention of child maltreatment (26) and a systematic review of child maltreatment prevention reviews, (27) by reviewing recent reviews of maltreatment prevention interventions (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)., including home visiting, (28)(29)(30), parenting-training programmes, (31,32) sexual abuse prevention programmes, (33,34) universal campaigns to prevent physical abuse, (35) behavioural and counseling interventions,(36) detection of child maltreatment, (37) and three review studies on prevention of child maltreatment. (38)(39)(40) The social protection review examined five systematic reviews that focused on the effects of social programmes, including conditional and unconditional cash transfers and microcredit schemes.…”
Section: Panel 1: Methods and Search Strategy For Selection Of Intervmentioning
confidence: 99%
See 1 more Smart Citation
“…(25) A meta-analysis of education programmes was conducted to determine non-cognitive developmental benefits of parenting and early childhood education programmes, as this information was not available in existing systematic reviews. The maltreatment review updated the Lancet 2009 series article on prevention of child maltreatment (26) and a systematic review of child maltreatment prevention reviews, (27) by reviewing recent reviews of maltreatment prevention interventions (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)., including home visiting, (28)(29)(30), parenting-training programmes, (31,32) sexual abuse prevention programmes, (33,34) universal campaigns to prevent physical abuse, (35) behavioural and counseling interventions,(36) detection of child maltreatment, (37) and three review studies on prevention of child maltreatment. (38)(39)(40) The social protection review examined five systematic reviews that focused on the effects of social programmes, including conditional and unconditional cash transfers and microcredit schemes.…”
Section: Panel 1: Methods and Search Strategy For Selection Of Intervmentioning
confidence: 99%
“…The maltreatment review updated the Lancet 2009 series for prevention of child maltreatment (22) and a systematic review of reviews of interventions to reduce child maltreatment, (23) in addition to a review of 14 recent reviews of maltreatment prevention interventions, including home visiting, (24)(25)(26), parenting-training programmes, (27,28) sexual abuse prevention programmes, (29,30) universal campaigns to prevent physical abuse,(31) behavioural and counseling interventions,(32) detection of child maltreatment, (33) and three review studies on prevention of child maltreatment. (34)(35)(36) The social protection review examined five systematic reviews that focused on the effects of social programmes, including conditional and unconditional cash transfers and microcredit schemes. (37)(38)(39)(40)(41) After examining the systematic reviews, the literature was searched for papers that had been published since the systematic reviews.…”
Section: Comment [Pb1]mentioning
confidence: 99%
“…The effects of CT on psychological development and symptomatology have been extensively studied during the past two decades (Anda et al, 2006;Cummings & Berkowitz, 2014;Dong et al, 2004;Dube et al, 2001;Geffner & Tishelman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers found that approximately one-half of callers to the warmline were parents and caregivers of children under the age of 6 years. In recalling the history of the Parenting Assistance Line and its relevance to child abuse prevention, one must consider how existing research indicates that lack of support can be a risk factor for the maltreatment of children (Cummings 2014) and how parental support was the primary concern of parents and caregivers of children under the age of 6 years. We also know that younger children are more at risk of child abuse and neglect (Children's Bureau 2013;Gelles and Cavanaugh 2005;McCoy and Keen 2009;World Health Organization 2002).…”
Section: Discussionmentioning
confidence: 99%